Effect of nitrogen, phosphorus and potassium levels on growth and yield of turmeric (Curcuma longa L.) in the hill zone of Karnataka - UTHAIAH, K S SHESHAGIRI, B C (Journal of Spices and Aromatic Crops, 1994)
A nutritional trial on turmeric (Curcuma longa) variety CO-1 conducted for three seasons at Regional Research Station, Mudigere, Karnataka indicated that a nutrient level of 120 : 60 : 120 kg NPK/ha is optimum for growth and yield of the crop in the hill zone of Karnataka.